The Satisfaction Analysis of Professional Placement Partners on The Performance of University Students - Busriadi, Busriadi; Zaki, Muhammad; Chusmita, Lina Ade; Hidayat, Ansori (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to see how the satisfaction of fieldwork practice partners (PKL) on student performance. The research method used is a combination of sequential explanatory models or designs, wherein the first stage of the research was carried out by quantitative methods and the second stage by qualitative methods. The instruments analyzed are aspects of the quality of activities, aspects of Human Resource Competence (HR), and aspects of activity productivity. The results of the three aspects that have been analyzed received excellent and positive responses. For this reason, it can be said that the instruments used in this study were appropriate. It can be proven that the quality of activity quality (KMK) received a good and positive response of as much as 68%. In addition, the satisfaction of partner companies with the Productivity of PKL activities has a positive relationship of 62.5%. Meanwhile, the satisfaction of partner companies concerning Human Resource Competence (KSDM) also has an excellent positive relationship of 68.8%. Efforts to maintain and improve student performance and partner satisfaction are tangible manifestations of creating better student performance.